Effect of parameters on reduction behaviour of preheated converter sludge pellets in grate-rotary kiln process. (9th August 2018) - Long, Hu; Jia, Yan Zhong; Liang, De Lan; Bai, Ming Hua; Ren, Su Bo
ABSTRACT: Effects of parameters including temperature, time and coal ratio on the reduction behaviour of preheated iron-bearing converter sludge pellets in a simulated rotary kiln are studied through orthogonal tests. ANOVA analyses show that reduction time and temperature have remarkable influence on the metallisation degree, occupying 55.02 and 30.08% of the total contribution, while temperature is the most significant factor affecting the compressive strength, with 90.98% contribution. The metallisation degree increases with the increasing time from 1.5 to 2.5 h, and first increases and then decreases with the increasing temperature from 1000 to 1100°C. The compressive strength increases with the increasing temperature. Under the optimal condition of temperature 1050°C, time 2.5 h, coal ratio 1.3, the metallisation degree is 72.92%, and the compressive strength is 1310 N/p, which satisfies the requirement of iron burden for blast furnace.